Structure and properties of germanium phosphate based glasses [electronic resource] - 218458 Abdel Wahab Mohamed Ali Hussein (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2006